The interface free energy: comparison of accurate Monte Carlo results for the 3D Ising model with effective interface models - Caselle, M.; Hasenbusch, Martin; Panero, Marco (Journal of high energy physics, 2007)
We provide accurate Monte Carlo results for the free energy of interfaces with periodic boundary conditions in the 3D Ising model. We study a large range of inverse temperatures, allowing to control corrections to scaling. In addition to square interfaces, we study rectangular interfaces for a large range of aspect ratios u = L1/L2. Our numerical results are compared with predictions of effective interface models. This comparison verifies clearly the effective Nambu-Goto model up to two-loop order. Our data also allow us to obtain the estimates Tc/(σ)1/2 = 1.235(2), m0++/(σ)1/2 = 3.037(16) and R+ = f+2σ0 = 0.387(2), which are more precise than previous ones.